FREQUENTLY AILING CHILDREN’S: HOW TO PROTECT A CHILD? - M.V. Krasnov; V.M. Krasnov (Вопросы современной педиатрии, 2010)
Authors present literature and proper data on effectiveness of vitamin-mineral complex Pikovit in syrup and tablets for the health improvement in frequently ailing children. Authors prove clinical and laboratory effect of vitamin-mineral complex.Key words: frequently ailing children, health improvement, vitamins, minerals.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2010;9(2):161-164)